Controlling the Periodically Ordered Nanostructures in Ceramics: A Macromolecule‐Guided Strategy. Issue 1 (20th November 2019) - Guo, Qing‐Yun; Zhang, Bo‐xing; Feng, Xueyan; Yan, Xiao‐Yun; Su, Zebin; Cheng, Stephen Z. D.; Yue, Kan
Abstract: Microscopic structures have a significant influence on the properties of ceramics. The development of macromolecular self‐assembly has allowed for control over microscopic structures of ceramics to prepare ceramics with diverse compositions and ordered nanostructures. Herein, recent progress in the preparation of ceramics with periodically ordered nanostructures guided by phase‐separated macromolecules are reviewed, which can be summarized as a general strategy termed the "macromolecule‐guided strategy." Moreover, two different subcategories, namely, the macromolecule‐templated method and the macromolecule‐precursor method, are illustrated. In the former method, amphiphilic macromolecules are used as templates to guide the assembly of inorganic species into ordered nanostructures, which are subsequently converted into ceramics; in the latter method, amphiphilic macromolecules containing non‐volatile elements are used as the single‐source precursors for ordered ceramics. It is believed that the unique diversity and tunable features of macromolecular self‐assembly might offer unprecedented opportunities in the development of functional ceramics for various applications. Abstract : A macromolecule‐guided strategy to control periodically ordered nanostructures of ceramics is reviewed. Phase‐separated macromolecules serve as templates to guide the assembly of inorganic species, or contain non‐volatile elements by themselves, to form well‐ordered hybrids containing non‐volatile elements. Pyrolysis of hybrids results in the formation of ceramics with periodically ordered nanostructures.